Majas Hiperbola Pada Album Bootleg Karya Kenshi Yonezu - Ramfarel Irawan; Damai Yani (Universitas Negeri Padang, 2023)
Hyperbole or kochouhou ( 誇 張 法 ), also known as hyperbole, is a method or way of expressing something with great exaggeration to describe an actual situation. It is used to give a strong emphasis or impact in the delivery of a message. However, many people, especially Japanese language learners in Indonesia do not really understand how to use hyperbole in song lyrics especially Japanese songs. This research aims to describe the types and meanings of hyperbole in Bootleg album. This type of research is qualitative research with descriptive analysis methods and data collection using listening techniques, followed by free listening techniques and note taking techniques supported by source triangulation theory and theory. The data of this research are lyrics that contain hyperbole and the data source used is Bootleg album. From the research results. The research found 32 data of hyperbole which are divided into 5 types, namely: Figurative hyperbole (Chokuyu Na Kochouhou) 18 data, false hyperbole (Uso no Kochouhou) 5 data, hyperbole referring to body parts or physical conditions (Shintaiteki Na Kochouhou) 1 data, hyperbole referring to feelings (Shinjou Na Kochouhou) 6 data, and logical hyperbole (Ronriteki Na Kochouhou) 2 data.